Eine oligozäne Dolinenfüllung in der Iserlohner Kalksenke - Wenzens, Gerd (ERDKUNDE, 1974)
A solution doline which has sunk to the 300 metre level of the Iserlohn depression has been filled in synsedimentary fashion with upper Oligocene marine sands, interbedded clays, loams and the remnants of fossil soils. While the marine sediments identify the Iserlohn limestone depression as a small arm of the Oligocene sea which stretched from Wuppertal to Balve, the clays, loams and soil remnants indicate a number of land phases. Orographically, the lime stone depression is an erosion surface and indicates con siderable late Tertiary dissection of the northern Sauerland. The fact that the 300 metre level within the Iserlohn lime stone depression is of at least Upper Oligocene age provides a datum-line for the stratigraphic sequencing of Tertiary surfaces in the Sauerland.